2013 6th International Workshop on Cooperative and Human Aspects of Software Engineering (CHASE) 2013
DOI: 10.1109/chase.2013.6614738
|View full text |Cite
|
Sign up to set email alerts
|

Improving developer participation rates in surveys

Abstract: Abstract-Doing high quality research about the human side of software engineering necessitates the participation of real software developers in studies, but getting high levels of participation is a challenge for software engineering researchers. In this paper, we discuss several factors that software engineering researchers can use when recruiting participants, drawn from a combination of general research on survey design, research on persuasion, and our experience in conducting surveys. We study these factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 30 publications
(33 reference statements)
1
87
0
1
Order By: Relevance
“…Furthermore, it was explained that the results would only be used anonymously but that it was also possible to leave behind an email address in order to receive the results when the study is completed. Lastly, as monetary prizes can increase response rates [145], it was announced that one lucky participant would receive an Amazon gift card worth 50 dollars.…”
Section: Designing the Complete Surveymentioning
confidence: 99%
“…Furthermore, it was explained that the results would only be used anonymously but that it was also possible to leave behind an email address in order to receive the results when the study is completed. Lastly, as monetary prizes can increase response rates [145], it was announced that one lucky participant would receive an Amazon gift card worth 50 dollars.…”
Section: Designing the Complete Surveymentioning
confidence: 99%
“…Some works have reported a low rate of participation, what have motivated recent investigation on this topic [33]. We report the following factors and procedures we used to invite developers.…”
Section: Survey Samplingmentioning
confidence: 99%
“…They helped us to achieve a reasonable number of participants and improve our response rate. We apply here the same terminology used in [29] [27] [33].…”
Section: Survey Samplingmentioning
confidence: 99%
“…We used the time frame of January 1, 2017 to August 1, 2017 to minimize the amount of organizational churn during the time period and identify employees' activity in their current role and team. As we have found that incentives can increase participation [71], survey participants were entered into a raffle for four $25 gift cards. We received 507 valid answers (20% response rate).…”
Section: Interviewsmentioning
confidence: 99%